Volatility of amorphous solid water - Nachbar, Mario; Duft, Denis; Leisner, Thomas (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2018)
Amorphous solid water is probably the most abundant form of solid water in the universe. Its saturation vapor pressure and thermodynamic properties, however, are not well known. We have investigated the saturation vapor pressure over vapor-deposited amorphous ice at temperatures between 133 and 147 K using a novel experimental method. The new method determines the absolute vapor pressures and the sublimation rates by measuring the mass growth rates of ice-covered nanoparticles under supersaturated water vapor conditions. We find that the vapor pressure of amorphous solid water is up to a factor of 3 higher than that predicted by current parameterizations, which are based in part on calorimetric measurements. We demonstrate that the calorimetric measurements can be reconciled with our data by acknowledging the formation of nanocrystalline ice as an intermediate ice phase during the crystallization of amorphous ice. As a result, we propose a new value for the enthalpy of crystallization of amorphous solid water of ΔH = 2312 ± 227 J/mol, which is about 1000 J/mol higher than the current consensus. Our results shine a new light on the abundance of water ice clouds on Mars and mesospheric clouds on Earth and may alter our understanding of ice formation in the stratosphere.
Gesehen am 04.12.2019